An n‐Type Polythiophene Derivative with Excellent Thermoelectric Performance. (22nd March 2023) - Deng, Sihui; Dong, Changshuai; Liu, Jian; Meng, Bin; Hu, Junli; Min, Yang; Tian, Hongkun; Liu, Jun; Wang, Lixiang
Abstract: Typical n‐type conjugated polymers are based on fused‐ring electron‐accepting building blocks. Herein, we report a non‐fused‐ring strategy to design n‐type conjugated polymers, i.e. introducing electron‐withdrawing imide or cyano groups to each thiophene unit of a non‐fused‐ring polythiophene backbone. The resulting polymer, n‐PT1, shows low LUMO/HOMO energy levels of −3.91 eV/−6.22 eV, high electron mobility of 0.39 cm 2  V −1  s −1 and high crystallinity in thin film. After n‐doping, n‐PT1 exhibits excellent thermoelectric performance with an electrical conductivity of 61.2 S cm −1 and a power factor ( PF ) of 141.7 μW m −1  K −2 . This PF is the highest value reported so far for n‐type conjugated polymers and this is the first time for polythiophene derivatives to be used in n‐type organic thermoelectrics. The excellent thermoelectric performance of n‐PT1 is due to its superior tolerance to doping. This work indicates that polythiophene derivatives without fused rings are low‐cost and high‐performance n‐type conjugated polymers. Abstract : An n‐type non‐fused‐ring conjugated polymer is developed by introducing electron‐withdrawing imide or cyano groups to each thiophene unit of polythiophene backbone. The resultant polymer shows low LUMO/HOMO energy levels and highly ordered crystallite structure, leading to excellent thermoelectric performance after n‐doping.